Musical Echoes: South African Women Thinking in Jazz. Carol Ann Muller and Sathima Bea Benjamin. 2011. Durham, NC: Duke University Press. 348 pp. - Monson, Ingrid (International Library of African Music, 2012)
pages: 170-172
Keywords: South Africa; African Music